Conflict: a cause and effect of hunger - Messer, Ellen; Cohen, Marc J.; Marchione, Thomas (Woodrow Wilson International Center for Scholars, 2001)
Ensuring food security -- especially in Africa -- depends on breaking cycles of hunger and conflict. Whether one believes that (a) environmental scarcities (including food insecurity) can cause conflict, or (b) that conflict is primarily caused by political factors, it is indisputable that access to food is always disrupted by conflict. Much has been written about the linkages between environmental scarcities, hunger, and conflict. This article (a) highlights certain gaps in the information about the steps that lead from hunger to conflict, and then (b) suggests policies and actions to break these connections.